Treatment of Venous Thromboembolism in Pediatric Patients - Malec, Lynn; Young, Guy (Frontiers in Pediatrics, 2017)
Given the increased incidence of venous thromboembolism (VTE) in pediatric patients which has been associated with increased survival of medically complex patients and increased use of invasive supportive measures, it is important to understand treatment options and unique aspects of anticoagulant use in children. The objective of this mini-review is to outline the goals of treatment, treatment options and adverse events associated with use of anticoagulants in pediatric patients with VTE.